Basic English - Jex, William W.; Langer, Mona E.; Langer, Peter (New York Video Aided Instruction, 1989)
A thirty five-lesson, interactive course in basic English designed for native speakers of other languages. Each lesson contains instruction in listening, speaking, reading and writing. Grammar structures are clearly iullustrated with easy-to-follow video graphics.
VHS.
Keywords: English language -- Sound recordings for foreign speakers; English language -- Self-instruction.; Language